Mechanical Circulatory Support for Single Ventricle Failure - Griselli, Massimo; Sinha, Raina; Jang, Subin; Perri, Gianluigi; Adachi, Iki (Frontiers in Cardiovascular Medicine, 2018)
Mechanical circulatory support (MCS) for failing single ventricle (SV) physiology is a complex and challenging problem, which has not yet been satisfactorily addressed. Advancements in surgical strategies and techniques along with intensive care management have substantially improved the outcomes of neonatal palliation for SV physiology, particularly for hypoplastic left heart syndrome (HLHS). This is associated with a steady increase in the number of SV patients who are susceptible to develop heart failure (HF) and would potentially require MCS at a certain stage in their palliation. We have reviewed the literature regarding the reported modalities of MCS use in the management of SV patients. This includes analysis of various devices and strategies used for failing circulation at distinct stages of the SV pathway: after neonatal palliation, after the superior cavo-pulmonary connection (SCPC), and after total cavo-pulmonary connection (TCPC).